Karakteristik Fisikokimia Nib Kakao dengan Berbagai Jenis Fermentasi dan Penyangraian Metode Puffing Gun - Sari, Dwi Indah Permata; Purwanto, Eko Heri; Aunillah, Asif; Rosidah, Umi (Jurnal Teknologi dan Industri Pangan, 2025)
Improving the quality of cocoa beans poses a great challenge when dealing with raw unfermented beans, as this process requires a relatively longer time. Furthermore, the roasting process, which is crucial in flavor development, can reduce the polyphenol content and antioxidant activity of cocoa beans. This study aimed to analyze the effects of different cocoa bean fermentation and puffing gun roasting methods on physicochemical characteristics of cocoa nibs. This research was carried out with two types of treatment: variations in puffing pressure (3, 4, and 5 Bar) and type of coco beans as raw material (unfermented, spontaneously fermented, and fermented using ragi tape). The results showed that carbohydrate content increased with increasing pressure of puffing gun; but otherwise, increasing puffing pressure decreased water content, fat content, total polyphenols, antioxidant activity, and hedonic scores for taste and aroma. The type of raw material treatment significantly influenced ash content, carbohydrates, L* (lightness) and a* (redness) color intensity, fat content, antioxidant activity, taste, and aroma. Cocoa nibs fermented spontaneously and roasted at a pressure of 3 Bar had the highest fat content, antioxidant activity, and the most favorable sensory scores for taste and aroma. The results of this study provide important insight for developing cocoa bean processing techniques that preserve desirable physicochemical properties and improve consumer preference.